A new validated instrument to assess sustainability perception among university students - Laura Salahange; Jesús Sánchez-Martín; María A. Dávila-Acedo; Florentina Cañada-Cañada (Discover Sustainability)
Abstract Promoting sustainability within university institutions entails conducting assessments to lay the groundwork for developing educational methodologies. This article presents the validation of a quantitative 36-item scale questionnaire to measure university students' perceptions towards sustainability. A total of 285 university students from different Spanish Universities participated in completing the questionnaire. The reliability and validity of the instrument were statistically assessed through Cronbach’s alpha and confirmatory factor analysis. The questionnaire is of mixed character, combining 6-point Likert scale questions (ranging from “Strongly disagree” to “Strongly agree”), closed and open-ended questions. It was structured into six dimensions: knowledge, attitude, willingness to act, behavior, self-efficacy, and affective. The first five dimensions were confirmed by a confirmatory factor analysis, demonstrating a good fit level in the model (RMSEA = 0.043, CFI = 0.972, SRMR = 0.076, TLI = 0.970 and X2/df = 1.45), while the affective dimension was analyzed using a qualitative approach. Internal reliability, found using Cronbach’s alpha, varies between 0.737 and 0.909. The results show that the instrument meets the validity and reliability criteria. Consequently, a valuable tool for academic utilization is suggested, offering a diagnostic and monitoring mechanism for evaluating sustainability perceptions, a topic that has recently garnered significant attention.